2013
DOI: 10.1002/ab.21490
|View full text |Cite
|
Sign up to set email alerts
|

High testosterone levels and sensitivity to acute stress in perpetrators of domestic violence with low cognitive flexibility and impairments in their emotional decoding process: A preliminary study

Abstract: Hormonal and neuropsychological impairment in intimate partner violence (IPV) perpetrators could play a role in domestic violence. For characterizing whether there is a specific psychobiological response to stress, participants who had previously been jailed for IPV and controls were compared for testosterone and cortisol levels, tested for 2D:4D ratio (as an indicator of masculinization), and given several trait questionnaires and neuropsychological tests related to executive functions and theory of mind. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 87 publications
(87 reference statements)
12
71
0
2
Order By: Relevance
“…This is consistent with previous research in this field (Babcock et al, 2008;Holtzworth-Munroe & Smutzler, 1996;Marshall & Holtzworth-Munroe, 2010;RomeroMartínez, Lila, Catalá-Miñana et al, 2013;Romero-Martínez, Lila, Sariñana-González et al, 2013;. We also found that those emotional decoding impairments could be partially explained by self-reported impairments in attentional set shifting or switch costs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with previous research in this field (Babcock et al, 2008;Holtzworth-Munroe & Smutzler, 1996;Marshall & Holtzworth-Munroe, 2010;RomeroMartínez, Lila, Catalá-Miñana et al, 2013;Romero-Martínez, Lila, Sariñana-González et al, 2013;. We also found that those emotional decoding impairments could be partially explained by self-reported impairments in attentional set shifting or switch costs.…”
Section: Discussionsupporting
confidence: 82%
“…In line with these results, previous studies have demonstrated that violent offenders show significant deficits in attentional set shifting or larger attention switch costs in comparison with non-violent population (Bergvall, Wessely, Forsman, & Hansen, 2001). In fact, this attention deficit might explain not only the impaired emotion decoding process but also the executive domain deficits defined as a worse performance in tests like the Wisconsin Card Sorting Test, which has been previously reported in IPV perpetrators (Gracia et al, 2015;Romero-Martínez, Lila, Catalá-Miñana et al, 2013;Romero-Martínez, Lila, Sariñana-González et al, 2013;. Nonetheless, it is important to note that in our research we analyzed attention deficits with self-reports, although these subscales have been employed as successful inattention measures in previous studies in several populations (Polderman et al, 2013;Rusconi, Ferri, Viding, & Mitchener-Nissen, 2015;Sizoo et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…IPV perpetrators did not differ from controls in age (36.88 ± 2.59 and 34.82 ± 1.47, respectively), BMI (26.84 ± 3.34 and 27.20 ± 3.22, respectively) or sociodemographic variables (see details in Romero-Martínez et al, 2013b). Moreover, no differences were found in baseline values of cardiovascular variables.…”
Section: Participant Characteristics and Appraisal Scoresmentioning
confidence: 61%
“…Thus, it would be of great utility to develop a single neuropsychological battery for the assessment of the propensity for violence in the absence or presence of drug abuse, adjusting it to a series of tests tailored to this population subgroup. This, together with the consideration of diverse psychobiological variables shown to be relevant in violent people (Romero-Martínez et al, 2013a;2013b;Romero-Martínez, González-Bono, Lila, & Moya-Albiol, 2013;Romero-Martínez, Lila, Conchell, González-Bono, & Moya-Albiol, 2014;Romero-Martínez, Lila, Williams, González-Bono, & Moya-Albiol, 2013), would permit the development of intervention strategies that focus on these specific cognitive domains. …”
Section: Discussionmentioning
confidence: 99%